Eating rate and bite size were related to food intake across meals varying in portion size: A randomized crossover trial in adults. (1st January 2023) - Cunningham, Paige M.; Roe, Liane S.; Keller, Kathleen L.; Hendriks-Hartensveld, Anouk E.M.; Rolls, Barbara J.
Abstract: Serving larger portions leads to increased food intake, but behavioral factors that influence the magnitude of this portion size effect have not been well characterized. We investigated whether measures of eating microstructure such as eating rate and bite size moderated the portion size effect. We also explored how sensory-specific satiety (SSS; the relative hedonic decline of a food as it is eaten) was affected by eating microstructure and larger portions. In a randomized crossover design, 44 adults aged 18–68 y (66% women; 46% with overweight and obesity) ate lunch in the laboratory once a week for 4 weeks. The meal consisted of pasta that was varied in portion size (400, 500, 600, or 700 g) and 700 g of water. Meals were video-recorded to assess bite count and meal duration, which were used to calculate mean eating rate (g/min) and mean bite size (g/bite). At each meal participants also completed an assessment of SSS. The results showed that as larger portions were served, meal intake increased in a curvilinear manner (p < 0.0001). Measures of eating microstructure did not moderate the portion size effect but were related to intake across all portions; faster eating rate, larger bite size, higher bite count, and longer meal duration were associated with greater consumption at all meals (all p < 0.0001). SSS was not influenced by any measure of eating microstructure or by portion size (all p > 0.10). In summary, the portion size effect was not moderated by eating microstructure, but relatively faster eating rates and larger bite sizes at meals, along with large portions, combined to increase food intake.